LINGUISTIC, STRUCTURAL, AND COGNITIVE CHALLENGES IN INDONESIAN EFL STUDENTS' ARGUMENTATIVE WRITING - Jaya, Sinarman (University of Kuningan, 2025)
Argumentative writing remains challenging for EFL learners due to its demands for accurate language, logical organization, and critical thinking. Although previous studies have addressed these aspects individually, limited research has examined how linguistic, structural, and cognitive difficulties interact in students’ writing. This mixed-methods study investigated these interrelated challenges among 40 undergraduate students enrolled in an Essay Writing course at Universitas Muhammadiyah Bengkulu, Indonesia. Data were collected through essay analysis, student questionnaires, and semi-structured interviews. Quantitative analysis showed that 75% of students had difficulty with sentence complexity, 67% misused cohesive devices, and 82% lacked clear thesis statements. Structurally, 69% omitted counterarguments and exhibited weak coherence. Cognitively, 58% reported anxiety and low confidence, which negatively influenced their writing quality. A strong positive correlation (r = 0.72, p < 0.01) was found between language proficiency and essay organization. Following instructor feedback and guided instruction, 72% of students showed measurable improvement in their writing. Interview findings emphasized the perceived benefits of model texts, explicit feedback, and opportunities for revision in overcoming cognitive and structural barriers. This study contributes to the limited literature on the interplay of multiple constraints in EFL writing by offering an integrated view of the obstacles that students face. The findings suggest the need for a comprehensive instructional approach that simultaneously addresses linguistic accuracy, rhetorical structure, and cognitive support to enhance students’ argumentative writing competence in EFL classrooms.